Factorize: 4(x+y)² - 28(x+y) + 49y²
Answers
Answered by
4
if this ques has middle term 28y(x+y)
then by the formula (a-b)^2=a^2+b^2-2ab
[2 (x+y)-7y]^2
=(2x+2y-7y)^2
=(2x-5y)^2
then by the formula (a-b)^2=a^2+b^2-2ab
[2 (x+y)-7y]^2
=(2x+2y-7y)^2
=(2x-5y)^2
EmoLord:
Middle term isn't stated
Answered by
5
00000000000000000000
Attachments:
![](https://hi-static.z-dn.net/files/d55/f365e2b79c8f15985005e6d7edbad437.jpg)
Similar questions
India Languages,
9 months ago
Science,
9 months ago
Social Sciences,
9 months ago
English,
1 year ago
Math,
1 year ago
Physics,
1 year ago
Math,
1 year ago